Youth-friendly HIV self-testing: Acceptability of campus-based oral HIV self-testing among young adult students in Zimbabwe. - Andrea L Koris (Public Library of Science (PLoS), 2021)
Background Targeted HIV testing strategies are needed to reach remaining undiagnosed people living with HIV and achieve the UNAIDS' 95-95-95 goals for 2030. HIV self-testing (HIVST) can increase uptake of HIV testing among young people, but user perspectives on novel distribution methods are uncertain. We assess the acceptability, perceived challenges, and recommendations of young adult lay counselor-led campus-based HIVST delivery among tertiary school students aged 18-24 years in Zimbabwe. Methods We purposively sampled participants from an intervention involving campus-based HIVST using lay workers for distribution. We conducted in-depth interviews (IDIs) and focus group discussions (FGDs) among young adults from 10 universities and colleges in Zimbabwe who: (1) self-tested on campus; (2) self-tested off campus; and (3) opted not to self-test. We audio recorded and transcribed all interviews. Using applied thematic analysis, two investigators identified emergent themes and independently coded transcripts, achieving high inter-coder agreement. Results Of the 52 young adults (53.8% male, 46.1% female) interviewed through 26 IDIs and four FGDs, most IDI participants (19/26, 73%) favored campus-based HIVST, describing it as a more autonomous, convenient, and socially acceptable experience than other facility or community-based HIV testing services. Despite general acceptability, participants identified challenges with this delivery model, including: perceived social coercion, insufficient privacy and access to post-test counseling. These challenges influenced some participants to opt against self-testing (6/52, 11.5%). Recommendations for improved implementation included integrating secondary distribution of test kits and increased HIV counseling options into campus-based programs. Conclusions Barriers to HIV testing among young people are numerous and complex. As the number of new HIV infections among youth continue to grow worldwide, targeted strategies and youth friendly approaches that increase access to testing are needed to close the diagnostic coverage gap. This is the first study to describe young adult acceptance of campus-based delivery of HIVST by lay counselors in Zimbabwe.